PENGGUNAAN MEDIA GAMBAR SERI DALAM MENINGKATKAN KETERAMPILAN MENULIS CERITA SISWA DI KELAS ISDN 52 MATTIRO SOMPE KABUPATEN PINRANG - NORMAH, SITTI (Kuriositas: Media Komunikasi Sosial dan Keagamaan, 2015)
This research is classroom action researchwith recycle action, that includes planning, implementation, observation, and reflection. The datawasdata from activities of students during learning process of writing a storybased on a picture series as well as the data results of students in the learning process of writing using media pictures series. Data obtained by observation, testing and photo documentation. The results showed that in Cycle 1, moststudents are still lacking courage to sort pictures, stating the reason logically and write stories with a good writing. After giving some actions in cycled II, students have dared to sort the pictures as well as express logical reason eventhough the reason less precise , as well as the manner of writing. After the third cycle, there a big progress which the students able to put forward a logical reason in the sequence of pictures and writing stories with the correct writing. The conclusion in this research, by using picture series as mediacan improve studentsâ writing story skills in class I of SDN 52 MattiroSompePinrang.